Romanian Educational Management from The Perspective of Generation Z - Cătălina Sitnikov; Carmen Maria Mihalcea; Sofia Mihaela Romanescu (Ovidius University Annals: Economic Sciences Series, 2022)
In the coming period, the academic and organizational environment will face a significant influx of students (graduates) members of Generation Z, developed, trained and educated under a strong influence of the democratic Western paradigm, which requires communication systems and techniques specific to the generation digital within the processes of educational management and organizational management. The main purpose of the article is to analyze students who are members of Generation Z from the perspective of the value orientations that characterize them, both in the form of a transversal approach and a longitudinal comparative perspective, to formulate some general guidelines regarding optimal educational management. The objective of the research is to observe the perceptions, beliefs and opinions of students who are members of Generation Z and to formulate some general guidelines regarding optimal educational management, respectively optimal organizational management, from their perspective.